S.E.A-ing the Future: Orchestrating Regional Economic Advancement and Integration in ASEAN - Azzadin, Asyraf Aisy; Altaaf, Muhammad Rakha Landika; Putri, Rachmania Utami Tsalasa (Asean Study Center Lambung Mangkurat University, 2023)
The Association of Southeast Asian Nations is an organization that has lots of potential and challenges, from its large population to political barriers; however, it recognizes the need to improve and strengthen its capability to meet the expectations and needs of the changing times. This paper argues that aside from the external and internal issues ASEAN needs to face, such as internal solidarity and the decline of ASEAN’s central role in the Indo-Pacific, ASEAN also needs to adapt to the changing world, with digital technology transforming the world. In the discussion section of the paper, it further provides mitigating initiatives to tackle the issues and maximize the benefits ASEAN receives, and it suggests the establishment of a central sectoral body capable of overseeing the implementation of the initiatives.